Downregulation of hepatic multi-drug resistance protein 1 (MDR1) after copper exposure. Issue 9 (14th August 2017) - Groba, Sara Reinartz; Guttmann, Sarah; Niemietz, Christoph; Bernick, Friedrich; Sauer, Vanessa; Hachmöller, Oliver; Karst, Uwe; Zischka, Hans; Zibert, Andree; Schmidt, Hartmut H.
Abstract : MDR1 is implicated in the modulation of hepatocyte copper transport following long-term exposure possibly by direct import or indirectly by reducing toxicity at subcellular localizations, including organelles like mitochondria. Abstract : Copper homeostasis is strictly regulated in mammalian cells. We investigated the adaptation of hepatocytes after long-term copper exposure. Copper-resistant hepatoma HepG2 cell lines lacking ATP7B were generated. Growth, copper accumulation, gene expression, and transport were determined. Hepatocyte-like cells derived from a Wilson disease (WD) patient and the liver of a WD animal model were also studied. The rapidly gained copper resistance was found to be stable, as subculturing of cells in the absence of added copper (weaning) did not restore copper sensitivity. Intracellular copper levels and the expression of MT1 and HSP70 were increased, whereas the expression of CTR1 was reduced. However, the values normalized after weaning. In contrast, downregulation of multi-drug resistance protein 1 ( MDR1 ), encoding P-glycoprotein (P-gp), was shown to be permanent. Calcein assays confirmed the downregulation of MDR1 in the resistant cell lines. MDR1 knockdown by siRNA resulted in increased copper resistance and decreased intracellular copper. Treatment of the resistant cells with verapamil, a known inducer of MDR1, was followed by increased copper-induced toxicity. Downregulation of MDR1 was also observed in hepatocyte-like cells derived from a WD patient after copper exposure. In addition, MDR1 was downregulated in Long-Evans Cinnamon rats when the liver copper was elevated. The results indicate that downregulation of MDR1 is an adaptation of hepatic cells after sustained copper exposure when ATP7B is non-functional. Our data add to the versatile functions of MDR1 in the hepatocyte and may have an impact on the treatment of copper-related diseases, prominently WD.